Cheerleaders or Critics?: Australian and Indian sports journalists in the contemporary age. Issue 5 (28th May 2017) - English, Peter
Abstract : Sports journalists have often been criticised for their casual approach to work and cheerleading content in stories. This style of journalism contrasts with the traditional norms of objectivity employed in other areas of newsrooms. It is also opposed to the critical watchdog role considered essential to objective reporting. To examine how sports journalists operate in relation to being cheerleaders or critical watchdogs, this study utilises the Australia–India Test cricket series of 2014–15 as a platform to investigate sports journalists' views, and the content they produce. It employs in-depth interviews with 18 sports journalists from Australian and Indian newspaper organisations in conjunction with a content analysis of 1265 articles from eight Australian and Indian publications. This allows a comparison of the perceptions of the sports journalists with what they are producing in their stories. Selecting a major international event with historical importance, such as the Australia–India Test series, is important in providing an example for analysis of whether contemporary sports journalists have confused the roles of reporter and supporter. An important finding in this study, given the long-standing criticism of sports journalists, was a considerably higher proportion of critical reports about the series in both nations than of cheerleading. Overall, this was consistent with the perceptions of the sports journalists in the in-depth interviews.